Structural basis for protein-protein interactions in the 14-3-3 protein family. - Yang, X; Lee, W; Sobott, F; Papagrigoriou, E; Robinson, C; Grossmann, J; Sundström, M; Doyle, D; Elkins, J (2006)
The seven members of the human 14-3-3 protein family regulate a diverse range of cell signaling pathways by formation of protein-protein complexes with signaling proteins that contain phosphorylated Ser/Thr residues within specific sequence motifs. Previously, crystal structures of three 14-3-3 isoforms (zeta, sigma, and tau) have been reported, with structural data for two isoforms deposited in the Protein Data Bank (zeta and sigma). In this study, we provide structural detail for five 14-3-3 isoforms bound to ligands, providing structural coverage for all isoforms of a human protein family. A comparative structural analysis of the seven 14-3-3 proteins revealed specificity determinants for binding of phosphopeptides in a specific orientation, target domain interaction surfaces and flexible adaptation of 14-3-3 proteins through domain movements. Specifically, the structures of the beta isoform in its apo and peptide bound forms showed that its binding site can exhibit structural flexibility to facilitate binding of its protein and peptide partners. In addition, the complex of 14-3-3 beta with the exoenzyme S peptide displayed a secondary structural element in the 14-3-3 peptide binding groove. These results show that the 14-3-3 proteins are adaptable structures in which internal flexibility is likely to facilitate recognition and binding of their interaction partners.